“My sexuality sort of complicates things”: community and support for Lesbian, Bisexual and Queer People in Lusaka - Chela, Efemia Christiana (My University, 2022)
This thesis explores how LBQ women and female-bodied non-binary people in Lusaka, Zambia access support and build community in a context where their sexual identity is criminalised by the state and denigrated by society and the church. This ethnographic research based on one-on-one interviews situates the six research participants’ gender identity and sexual orientation within broader discourses about Zambian nationhood, womanhood and heterosexuality. It investigates how the participants use a combination of digital counterpublics, in-person support and nightlife to form a nascent subcultural community.
A dissertation submitted in partial fulfilment of the requirements for the award of the degree of Master of Arts in Development Studies to the Faculty of Humanities, University of the Witwatersrand, 2021